Development of a novel hydrogel for skin regeneration - Miguel, Sónia Alexandra Pereira (2018)
Skin lesions are traumatic events that lead to increased fluid loss, infections, scars formation and the appearance of immunocompromised regions. The loss of skin integrity can result in significant physiological imbalances and disability or even death. So far, different wound dressings have been developed. Among them, hydrogels are the most applied. Herein, a thermoresponsive hydrogel was produced using chitosan and agarose formed at body temperature (37°C), in order to verify their applicability in the treatment of wounds. Hydrogel bactericidal activity, biocompatibility, morphology, porosity and wettability were characterized by confocal microscopy, MTS assay and SEM. The attained results revealed that hydrogel has a pore size (90–400 µm) compatible with cellular internalization and proliferation. A bactericidal activity was observed for hydrogels containing more than 188 µg/mL of chitosan. The results obtained demonstrated that this 3D network has the suitable properties for improving the healing process of cutaneous wounds.